Modelling and verification of large-scale sensor network infrastructures - Sevegnani,M; Kabac,M; Calder,M; McCann,JA (IEEE, 2018)
Large-scale wireless sensor networks (WSN) are increasingly deployed and an open question is how they can support multiple applications. Networks and sensing devices are typically heterogeneous and evolving: topologies change, nodes drop in and out of the network, and devices are reconfigured. The key question we address is how to verify that application requirements are met, individually and collectively, and can continue to be met, in the context of large-scale, evolving network and device configurations. We define a modelling and verification framework based on Bigraphical Reactive Systems (BRS) for modelling, with bigraph patterns and temporal logic properties for specifying application requirements. The bigraph diagrammatic notation provides an intuitive representation of concepts such as hierarchies, communication, events and spatial relationships, which are fundamental to WSNs. We demonstrate modelling and verification through a real-life urban environmental monitoring case-study. A novel contribution is automated online verification using BigraphER and replay of real-life sensed data streams and network events by the Cooja network simulator. Performance results for verification of two application properties running on a WSN with up to 200 nodes indicate our framework is capable of handling WSNs of that scale.